Transcriptomic Analysis of Two Lentinula edodes Genotypes With Different Cadmium Accumulation Ability - Yu, Hailong; Li, Qiaozhen; Shen, Xiufen; Zhang, Lujun; Liu, Jianyu; Tan, Qi; Li, Yu; Lv, Beibei; Shang, Xiaodong (Frontiers in Microbiology, 2020)
Lentinula edodes, also known as Xiang’gu, is commonly eaten in cultures around the world. However, L. edodes is particularly susceptible to enrichment with heavy metals, particularly cadmium (Cd), which is toxic to human health. Understanding the molecular mechanism and mining key genes involved in Cd enrichment will facilitate genetic modification of L. edodes strains. Two L. edodes genotypes, Le4625 (with higher Cd enrichment capability) and Le4606 (with lower Cd enrichment capability) were used in this study. The Cd concentrations in the mycelia of the tested genotypes differed significantly after Cd (0.1 mg/L) exposure; and the Cd content in Le4625 (1.390 ± 0.098 mg/kg) was approximately three-fold that in Le4606 (0.440 ± 0.038 mg/kg) after 7 h of Cd exposure. A total of 24,592 transcripts were assessed by RNA-Seq to explore variance in Cd accumulation. Firstly, differentially expressed genes (DEGs) were analyzed separately following Cd exposure. In comparison with Ld4625, Ld4606 showed a greater number of Cd-induced changes in transcription. In Ld4606, DEGs following Cd exposure were associated with transmembrane transport, glutathione transfer and cytochrome P450, indicating that these genes could be involved in Cd resistance in L. edodes. Next, Le4606 and Le4625 were exposed to Cd, after which DEGs were identified to explore genetic factors affecting Cd accumulation. After Cd exposure, DEGs between Le4606 and Le4625 encoded proteins involved in multiple biological pathways, including transporters on the membrane, cell wall modification, oxidative stress response, translation, degradation, and signaling pathways. Cd enrichment in cells may activate MAPK signaling and the anti-oxidative stress response, which can subsequently alter signal transduction and the intracellular oxidation / reduction balance. Furthermore, several possible candidate genes involved in the Cd accumulation were identified, including the major facilitator superfamily genes, heat shock proteins, and laccase 11, a multicopper oxidase. This comparison of the transcriptomes of two L. edodes strains with different capacities for Cd accumulation provides valuable insight into the cultivation of mushrooms with less Cd enrichment and also serves as a reference for the construction of engineered strains for environmental pollution control.